The influence of video games in cinematographic language:: the “300” case and the Playstation aesthetic - Carreiro, Rodrigo (2011)
This essay analyzes the growing influence of the aesthetics and narrative components of videogames in contemporary movies, using the film “300”, by director Zack Snyder, as a case study. Editing, sound design and large-scale narrative – the division in three acts becomes more fragile, shifted by a structure in which the hero needs to overcome successive obstacles with a growing degree of difficulty – are some of the standards of what we could call Playstation Aesthetics. This variation of the poetics of cinema intensifies the so-called MTV Aesthetics, which was based in accelerated editing techniques and electronic-modified sounds, and has been prevailing since the 1980’s.